PENGARUH METODE LATIHAN HIGH INTENSTY INTERVAL TRAINING TERHADAP VO2MAX ATLET TARUNG DERAJAT PONPES DARUL ARIFIN JAMBI - RD.Benita Ramadan; Boy Indrayana; Bangkit Yudho Prabowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on the results of the author's observations, the Darul Arifin Jambi PONPES Darul Arifin Jambi athlete is suspected to still have aerobic endurance (VO2max) that is not optimal. This study aims to determine the effect of the High Intensity Interval Training (HIIT) training method on increasing athletes' VO2max. The study used an experimental method with a one group pretest-posttest design on 10 athletes selected using the purposive sampling technique. Data collection was conducted through VO2max tests before and after HIIT training treatments. Data were analyzed using normality test and paired sample t-test. The results showed that the average VO2max increased from 46.4 to 48.5 with a difference of 2.11. The results of the hypothesis test showed a significance value of p < 0.001 (< 0.05), so that there was a significant influence of the HIIT training method on the increase in VO2max of Tarung Derajat athletes of PONPES Darul Arifin Jambi. Thus, the HIIT method can be used as an alternative to exercise to improve the aerobic endurance of athletes.